PSYCHOLOGISM IN LITERATURE: CONCEPTUAL FOUNDATIONS, ARTISTIC FUNCTIONS, AND GENRE-FORMING POTENTIAL - Umurova G.X.; Dosaliev K.S. (Sciental Journals Publishing, 2025)
This article synthesizes contemporary scholarly perspectives on psychologism in literature, examining its conceptual foundations, artistic functions, and role in genre development. The study highlights psychologism as both a method of representing characters’ inner worlds and a structural mechanism shaping narrative form. By integrating theoretical and stylistic approaches across recent research traditions, the article systematizes current understandings of how psychologism influences character construction, narrative organization, and the evolution of literary genres.
Keywords: Psychologism, literary criticism, artistic method, narrative psychology, genre development, inner world, character construction, narrative structure, artistic expression, literary theory.